Mapping Socio-Economic Diversity of Kollam (Quilon), India - Dr. Nisar Khan, Ankita Mangalik, Aamir Khan, Ajay Singhal (International Journal of Advanced Science and Technology, 2020)
This paper discusses the mapping of socio-economic information on the city maps to bring spatial dimension to the statistical understanding of the city. The objective of this exercise is to determine how spatial understanding of socio-economic data and phenomenon in a city can enable the urban planners and city administrators in formulating and implementing more effective projects and schemes. As in India and many developing countries the urban planning exercises are largely based on the statistical information, this paper discusses the significance of the maps and the methodology adopted to create them.